THE IMPACT OF FAST FOOD ON EARLY CHILDHOOD HEALTH - Khairunnisa Ulfadhilah (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2024)
Abstract Children's health is supported by a healthy lifestyle and nutritional intake that can support children's growth and development more optimally, but there are still some fathers and mothers who do not realize the importance of the knowledge that nutritional intake will have an impact on growth. Children's appetites are different from adults, which affects growth and development, and children like foods such as nuggets and outside snacks which do not necessarily contain a lot of nutrition. Apart from that, if you eat food at home, it is guaranteed to be clean, but if you buy food outside, that's not necessarily the case, so you prioritize healthy food provided at home. The research was carried out by PAUD An-Nur descriptive qualitative methods to explain data collection techniques such as observation, interviews, and documentation at PAUD An-Nur. Knowing the above phenomenon, researchers want to research so that they can provide references for mothers and fathers to get into the habit of consuming nutritional intake with good nutrition and maintaining cleanliness. Keywords: Early Childhood, Fast Food, Nutrition, and Health     Abstrak Kesehatan pada anak ditunjang dari pola hidup yang sehat maupun asupan nutrisi yang mampu menunjang tumbuh kembang anak lebih optimal namun masih beberapa ayah ibu yang belum menyadari pentingnya pengetahuan asupan nutrisi akan berdampak pada pertumbuhan. Nafsu makan anak berbeda dengan orang dewasa berpengaruh pada tumbuh kembang, dan anak-anak menyukai makanan seperti nugget serta jajanan diluar yang belum tentu mengandung banyak gizi. Selain itu, jika makanan dirumah sudah tentu terjamin kebersihan namun jika membeli makanan diluar belum tentu maka dari itu mengutamakan makanan sehat yang disediakan saat dirumah. Penelitian dilakukan PAUD An-Nur metode kualitatif deskriptif untuk menjelaskan kemudian teknik pengumpulan data seperti observasi, wawancara, dan dokumentasi di PAUD An-Nur. Mengetahui fenomena diatas maka peneliti ingin melakukan riset sehingga mampu berikan referensi untuk ayah ibu untuk pembiasaan mengkonsumsi asupan nutrisi dengan gizi yang baik maupun dijaga kesebersihan. Kata Kunci : Anak Usia Dini, Makanan Cepat Saji, Gizi, dan Kesehatan